Development of high-throughput lacrimal gland organoid platforms for drug discovery in dry eye disease - Teerapat Rodboon; Supansa Yodmuang; Risa Chaisuparat; Joao N. Ferreira (SLAS Discovery, 2022)
Dysfunction and damage of the lacrimal gland (LG) results in ocular discomfort and dry eye disease (DED). Current therapies for DED do not fully replenish the necessary lubrication to rescue optimal vision. New drug discovery for DED has been limited perhaps because in vitro models cannot mimic the biology of the native LG. The existing platforms for LG organoid culture are scarce and still not ready for consistency and scale up production towards drug screening. The magnetic three-dimensional (3D) bioprinting (M3DB) is a novel system for 3D in vitro biofabrication of cellularized tissues using magnetic nanoparticles to bring cells together. M3DB provides a scalable platform for consistent handling of spheroid-like cell cultures facilitating consistent biofabrication of organoids. Previously, we successfully generated innervated secretory epithelial organoids from human dental pulp stem cells with M3DB and found that this platform is feasible for epithelial organoid bioprinting. Research targeting LG organogenesis, drug discovery for DED has extensively used mouse models. However, certain inter-species differences between mouse and human must be considered. Porcine LG appear to have more similarities to human LG than the mouse counterparts. We have conducted preliminary studies with the M3DB for fabricating LG organoids from primary cells isolated from murine and porcine LG, and found that this platform provides robust LG organoids for future potential high-throughput analysis and drug discovery. The LG organoid holds promise to be a functional model of tearing, a platform for drug screening, and may offer clinical applications for DED.